Розвиток навичок «Soft Skills» в контексті «Performance Management Skills» - Ровенська, В. В.; Смирнова, І. І.; Латишева, О. В.; Rovenska, V. V.; Latysheva, O. V.; Smyrnova, I. I. (Національний авіаційний університет, 2023)
У статті з’ясована сутність та надана характеристика «soft skills», «performance management skills», які є основою для навичок "вищого порядку" («meta – skills»). Досліджено рекомендації закордонних фахівців щодо розвитку «soft skills». Встановлено, що мета-навички покликані розвивати мислення, спрямоване на розвиток, що дозволяє людям підготуватися до навчання впродовж усього життя, щоб розвивати нові компетенції в постійно мінливому робочому середовищі. В статті доведено, що на підставі розвитку «soft skills» будь-яка людина формує базу для розвитку постійних «meta-skills», що розширює її можливості працевлаштування, а також особистого та кар'єрного розвитку. У статті визначено важливість розвитку ключових навичок майбутніх фахівців незалежно від сфери діяльності. В статті представлено методика їх оцінювання за рівнем розвиненості навичок «soft skills» здобувачів вищої освіти. В статті доведено, що проведення такого оцінювання здобувачів дозволяє встановити «слабкі місця» за окремими складовими, наприклад, таким як: здатність до ефективної комунікації і ведення переговорів, навички роботи в команді, організаційні навички, тайм – менеджмент, адаптованість, креативність та інші.

This article aims to clarify the essence of "soft skills" and "performance management skills", which serve as the foundation for developing "higher-order" skills or "meta-skills". It reviews the recommendations of foreign experts on the development of soft skills and emphasizes that meta-skills are essential for cultivating a growth mindset that enables individuals to pursue lifelong learning and acquire new competencies in a constantly evolving work environment. The article argues that the development of soft skills lays the groundwork for cultivating permanent meta-skills, which can enhance employment prospects and personal and professional growth. It stresses the importance of developing key skills for future professionals across different fields of activity. The article also presents a methodology for assessing the level of soft skills development among higher education students, which can help identify areas of improvement, such as effective communication and negotiation, teamwork, organizational skills, time management, adaptability, creativity, and more. Moreover, the article contends that the development of soft skills, particularly in the context of performance management skills, can pave the way for the development of critical meta-skills. These meta-skills include stress tolerance, adaptability to change and challenges, self-management, effective communication, self-awareness, conflict resolution, cooperation, problem-solving, process innovation, adaptability to new realities, and proactivity. The article underscores the significance of these meta-skills in distinguishing oneself as a desirable candidate in the job market. The article identifies a list of necessary skills, such as the ability to negotiate and resolve conflicts, effectively interact with other people; the ability to adapt to constant changes and new reality; the ability to take responsibility, etc. Overall, the article highlights the interdependence of soft skills and meta-skills and stresses the importance of cultivating both sets of skills for achieving personal and professional success in the 21st century.
Development of Soft Skills in the context of Performance Management Skills
Keywords: soft skills; performance management skills; meta – skills; візуалізація; комунікація; освітній процес; здобувачі вищої освіти; visualization; communication; educational process; higher education students